1045 Determinants of treatment seeking behaviour following injury in Maringá, Brazil. (1st September 2016) - Toomey, Nicole; Vissoci, João Ricardo; Haglund, Michael; Staton, Catherine
Abstract : Background: Injury accounts for 6% of all disability adjusted life years lost. Current research on access to care and injury does not account for injury severity or levels of health care. Our project aims to determine what barriers to injury care arise in Brazil's universal health care system. Methods: Households were randomly selected in Maringá between May 2015 and September 2015. Demographic information was collected for the household; one individual was randomly selected to provide injury history. A chi-square analysis found the association between care-seeking and demographic variables. A preliminary significance level of α = 0.20 was used for inclusion of variables. A full multivariate logistic regression model and thirty reduced models were run. Mean squared estimate and Akaike Information Criterion were calculated to find the best predictive model. Results: Of the 2678 households and individuals sampled, 30.3% of individuals reported a lifetime injury. The univariate analysis found that gender (p = 0.034), injury cause (p < 0.001), race (p = 0.051), severity (p = 0.103) and insurance status (p = 0.026) were predictors of seeking care. Income, and age were included in the multivariate model due to significance in the literature. Based on this model, Burn victims had an increased odds of 7.92 of not seeking care compared to road traffic incident victims; this increased odds was also seen when stratifying by gender (OR = 9.49 for women, OR = 8.23 for males). For all injuries, being male had a protective effect on seeking care (OR = 0.64); women had higher odds of not seeking care (OR = 1.30) Conclusions: Cause of injury and socioeconomic status factors are a major predictor for seeking care, as are factors related to socioeconomic status. Cause potentially masked the effects of gender on care seeking. More research needs to be done on specific causes of injuries, the role of gender, and why socioeconomic status is still a barrier to care in a universal access system.